Historical evolution of the ophthalmologists training process in Cuba - Yudania Fouces Gutiérrez; Tania Rosa González García; Damaris Fuentes Pelier; Ricardo Hodelín Tablada (Centro Provincial de Información de Ciencias Médicas, 2021)
In Cuba, the training process in ophthalmology begins in the colonial and republican period, with an elitist character, that is modified after the triumph of the revolution. In that time the most important social activity was to extend the ophthalmological services up to the most isolated places to facilitate population care. Considering the above-mentioned the present study, aimed at characterizing the different stages of the Cuban ophthalmologists training process, was carried out. Some theoretical foundations that justify the necessity of the permanent and continuous training of the ophthalmologists are presented, taking into account their training peculiarities. It is concluded that in Cuban ophthalmology the professional training constitutes an important way to offer excellence services in all health care levels.